2010
DOI: 10.1590/s1516-31802010000600014
|View full text |Cite
|
Sign up to set email alerts
|

Acamprosate for alcohol dependence

Abstract: BACKGROUND: Alcohol dependence is among the main leading health risk factors in most developed and developing countries. Therapeutic success of psychosocial programs for relapse prevention is moderate, but could potentially be increased by an adjuvant treatment with the glutamate antagonist acamprosate.OBJECTIVE: To determine the effectiveness and tolerability of acamprosate in comparison to placebo and other pharmacological agents. CRITERIA FOR CONSIDERING STUDIES FOR THIS REVIEW:We searched the Cochrane Drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 1 publication
2
109
0
8
Order By: Relevance
“…We have simulated the potential effects of five different interventions: pharmacological treatment (based on the Cochrane reviews: (Rösner et al, 2010b;Rösner et al, 2010a) be an increase in pharmacological treatment, with brief interventions in hospitals being almost at the same level. If 20% of people with AD were treated, we estimated that 1.1% of all female alcohol-attributable deaths and 3.2% of all male alcohol-attributable deaths could be prevented within one year 2 .…”
Section: Effects Of Potential Treatment Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have simulated the potential effects of five different interventions: pharmacological treatment (based on the Cochrane reviews: (Rösner et al, 2010b;Rösner et al, 2010a) be an increase in pharmacological treatment, with brief interventions in hospitals being almost at the same level. If 20% of people with AD were treated, we estimated that 1.1% of all female alcohol-attributable deaths and 3.2% of all male alcohol-attributable deaths could be prevented within one year 2 .…”
Section: Effects Of Potential Treatment Interventionsmentioning
confidence: 99%
“…Pooled estimates of (Rösner et al, 2010b;Rösner et al, 2010a). For this simulation we are concerned with the differences in consumption between baseline and follow-up in the group receiving medications only.…”
Section: Infectious and Parasitic Diseasesmentioning
confidence: 99%
“…Acamprosate is a safe and welltolerated drug that does not affect craving (Umhau et al, 2011) but the risk to relapse. In a recent Cochrane Review Rösner et al (2010) summarized 24 randomized controlled trials (RCTs) on acamprosate, and concluded that acamprosate significantly reduces the risk of any drinking with a relative risk (RR) of 0.86. A RR of 1 means that there is no difference between placebo and treatment, whereas a RRo1 means that relapse occurs less frequently in the treatment group.…”
Section: Introductionmentioning
confidence: 99%
“…The logic is as follows: if calcium is the active moiety of acamprosate, and acamprosate does not produce a positive treatment effect in a randomized controlled trial, how then should calcium be associated with treatment outcome? Second, the now presented re-evaluation of the PREDICT data based on 76 acamprosate-and 25 placebo-treated patients with available plasma calcium levels was underpowered to detect any treatment effect (Rösner et al, 2010).Mann and colleagues bring up also two other points of criticism: they state 'While Spanagel et al (2014) used systemic application others have shown that the effects of intracerebral microinjection of sodium acamprosate are sitespecific (only effective in the bed nucleus of the stria terminalis) and dose dependent… These data provide evidence that sodium acamprosate is an active molecule affecting ethanol self-administration.' Others relate to a single experiment published as an abstract 12 years ago, in comparison to > 100 original investigations in rats that used systemic injections.…”
mentioning
confidence: 99%
“…The logic is as follows: if calcium is the active moiety of acamprosate, and acamprosate does not produce a positive treatment effect in a randomized controlled trial, how then should calcium be associated with treatment outcome? Second, the now presented re-evaluation of the PREDICT data based on 76 acamprosate-and 25 placebo-treated patients with available plasma calcium levels was underpowered to detect any treatment effect (Rösner et al, 2010).…”
mentioning
confidence: 99%